Kontribusi Wanita Nelayan dalam Kegiatan Pengolahan Abon Ikan di Kelurahan Pudai Kecamatan Abeli Kota Kendari - Abdullah, Sukmawati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
This research is aimed (1) to find out the contribution of fisherwomen in fish floss production at Abeli District, Kendari, (2) to find out the relationship between the fisherwomen characteristics and the fisherwomen's contribution in fish floss production. This research was carried out at the Joint Business Group of Pudai Sub-District, Abeli District, Kendari from October - November 2009. Data collection was performed through survey method. The primary data includes the fisherwomen's characteristics in fish floss production. The population in this research is all the 20 fisherwomen involved in fish floss production at Abeli District, Kendari. The sampling method was conducted through the census, which is in line with Sugiyono's statement (2007) that if all population is taken as a sample, then the method used is called saturated sampling or census. The variables in this research are the characteristics of fisherwomen such as age, educational background, family dependents, fisherwomen's experience, the frequency of attending extension program and media consumption; and fisherwomen's contribution in fish floss production which covers weeding, stewing, dressing, frying, and compaction. The obtained data in this research is qualitatively analyzed. Interval formula was used to classify the level of fisherwomen's contribution as high, medium, and low. Whilst Rank Spearman correlation was employed to test the relationship between both variables using SPSS software version 13. The result of the research reveals that most fisherwomen are at their productive age, high school graduates with medium family dependents, adequate experiences, frequent extension participants, and have high media consumption. The high contribution of fisherwomen in fish floss production are in terms of frying (60.00%), and compaction (85.00%). The median contribution of fisherwomen in fish floss production is in terms of weeding (55.00%), stewing (80.00%), and dressing (65.00%). Factors like fisherwomen's experience, the frequency of attending extension program and media consumption are significantly correlated, whilst age, educational background, and numbers of family dependents are not significantly correlated.